2016
DOI: 10.1016/j.apjtm.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

In vivo anticancer activity of maesopsin 4- O - β -glucoside isolated from leaves of Artocarpus tonkinensis A. Chev. Ex Gagnep

Abstract: These results indicate that TAT2 possesses clear antitumor activity. Due to its bioavailability and low toxicity, and the fact that it could be isolated in a large scale from A. tonkinensis leaves, the compound shows promise as a potential anticancer drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Medicinal properties of leaf and root extracts from A. tonkinensis have long been known and they are recorded in the textbooks of traditional Vietnamese and Chinese medicine. In particular, A. tonkinensis dried leaf decoction and its major active compounds auronol glycosides maesopsin 4-O-β-D-glucoside (TAT-2) and alphitonin-4-O-β-D-glucoside (TAT-6) were studied for their immunosuppressive activity in autoimmune diseases (Thuy et al, 2004;Thuy et al, 2017) and for antiproliferative effect in anti-cancer trials (Thuy et al, 2016). Vietnamese folk medicine practice to assume A. tonkinensis decoction against rheumatoid arthritis (RA) symptoms and several studies on experimental models of collagen-induced arthritis (CIA) (Ngoc et al, 2005;Dang et al, 2009;Adorisio et al, 2019) support the awareness of A. tonkinensis efficacy to contrast chronic inflammation, and destruction of bone and joints characterizing RA pathological picture.…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal properties of leaf and root extracts from A. tonkinensis have long been known and they are recorded in the textbooks of traditional Vietnamese and Chinese medicine. In particular, A. tonkinensis dried leaf decoction and its major active compounds auronol glycosides maesopsin 4-O-β-D-glucoside (TAT-2) and alphitonin-4-O-β-D-glucoside (TAT-6) were studied for their immunosuppressive activity in autoimmune diseases (Thuy et al, 2004;Thuy et al, 2017) and for antiproliferative effect in anti-cancer trials (Thuy et al, 2016). Vietnamese folk medicine practice to assume A. tonkinensis decoction against rheumatoid arthritis (RA) symptoms and several studies on experimental models of collagen-induced arthritis (CIA) (Ngoc et al, 2005;Dang et al, 2009;Adorisio et al, 2019) support the awareness of A. tonkinensis efficacy to contrast chronic inflammation, and destruction of bone and joints characterizing RA pathological picture.…”
Section: Introductionmentioning
confidence: 99%
“…Suppression of T cell proliferation and cytokine production by A. tonkinensis flavonoids may reduce disease severity after experimentally induced arthritis (Dang et al, 2009). In anti-cancer trials, maesopsin 4- O -β- D -glucoside (TAT-2) showed antiproliferative effects on acute myeloid leukemia cells and modulated expression of 19 cancer-related genes encoding proteins such as heme oxygenase-1, sulfiredoxin 1 homolog, and breast carcinoma amplified sequence 3 (Pozzesi et al, 2011), and exhibited in vivo anti-cancer effects (Thuy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This result was similar to some other studies. In vivo trials of the active ingredient TAT2 extracted from A. tonkinensis leaves have been shown to significantly inhibit tumor growth at 100 and 200 mg/kg body weight (Thuy TT et al, 2016). The AGN ethanol extract was tested against the growth of mouse Lewis Lung Carcinoma (LLC) allograftin syngenic mice or human PC-3 and DU145 prostate cancer xenograft in immunodeficient mice.…”
Section: Discussionmentioning
confidence: 99%